The jaguar's jewel - Roy, Ron, 1940-; Gurney, John Steven, 1962- (New York : Random House, 2000)
Dink and his friends use their detective skills to locate a giant emerald missing from a statue delivered to Uncle Warren's museum in New York City.
"A Stepping Stone book."
"J"--Spine.
3.1
3-6
Keywords: Museums -- Fiction; Stealing -- Fiction; New York (N.Y.) -- Fiction; Duncan, Dink (Fictitious character) -- Fiction; Mystery and detective stories; Museums -- Fiction; Theft -- Fiction; New York (N.Y.) -- Fiction; Duncan, Dink (Fictional character) -- Fiction; Mystery fiction